Estudos de sistemática molecular e de biogeografia histórica do bagre de água doce Pseudoplatystoma Bleeker, 1862 (Pimelodidae) na América do Sul - Costa, Luis Fernando Carvalho (Universidade Federal de São Carlos, 2010)
The catfishes of the Pseudoplatystoma genus are carnivore pimelodids, migratory and important for fisheries in all major river basins from South America. Only three species were recognized for the genus (P. corruscans, P. fasciatum and P. tigrinum), but a new revision raised to eight the number of species (P. fasciatum, P. punctifer, P. orinocoense, P. magdaleniatum, P. reticulatum, P. tigrinum, P. metaense and P. corruscans). Recently, Pseudoplatystoma was the subject of a molecular phylogeny study based on mitochondrial markers, where monophyletic clades where found for P. tigrinum, P. corruscans, P. reticulatum+P. punctifer+P. fasciatum and P. magdaleniatum. Despite these advances on the knowledge of the evolutionary history and systematics of the group, there are still questions to be answered. Thus, this study aimed a molecular phylogenetic analysis on Pseudoplatystoma to try to answer pendant questions about the systematics and taxonomy of the group, and propose a scenario for its diversification history in the geographic area of South America. In order to do this, we employed the mitochondrial Cytochrome b gene and introns from Rag1 and S7 genes, whose phylogenies were estimated by Maximum Likelihood using TREEFINDER software. Nodes were dated on BEAST software. It was shown that some Pseudoplatystoma species, resulting from the last revision of the genus, do not correspond to monophyletic groups or they were not significantly supported clades in all trees. The only monophyletic species in all markers were P. magdaleniatum and P. corruscans. Pseudoplatystoma orinocoense was a monophyletic lineage only on Cytochrome b. In light of these results, it is suggested that the old terminology P. fasciatum to be revalidated for the taxa here defined as P. fasciatum clade: P. punctifer (Amazon, Maranhão, Tocantins-Araguaia), P. reticulatum (Paraná-Paraguay) and P. fasciatum (Guyanas). Under the same rationale, P. tigrinum should be revalidated for Orinoco, given the paraphyletism of P. metaense. However, some cases of nonmonophyletic species in one or more markers may be due to incomplete lineage sorting, although this possibility needs to be investigated using other markers. The history of diversification of Pseudoplatystoma was the result of millions of years of evolution and and it was strongly influenced by the evolution of the South America geographical matrix. The biogeographic study allowed us to identify and date the important diversification events for the genus and relate them to the historical geomorphological and/or climate changes reported for South America, which would be the primary diversification causes for other freshwater fishes from the continent.
Keywords: Genética animal; Filogenia; Biogeografia; Sistemática; Peixes; Neotropical; Bagres; mtDNA; nDNA; Introns; Neotropical; Phylogeny; Catfish; mtDNA; nDNA; Introns; Biogeography; Molecular systematics; CIENCIAS BIOLOGICAS::ECOLOGIA